Aspek Perjanjian Waralaba Perspektif Hukum Perdata - Ranadi, Gladys Felicia; Urbanisasi, Urbanisasi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this paper is to find out the Franchise agreement in Indonesia based on Law Number 9 of 1995 and Government Regulation Number 42 of 2007 and its shortcomings compared to more developed countries which have prioritized their advantages. A franchise agreement is a type of agreement often used in medieval commerce. But for nearly a century, these contracts have been used by legal entities looking to transact and generate higher profits. Legally, this franchise agreement is regulated in Decree no. 16 of 1997 concerning Franchising, which is regulated in Decree no. 42 of 2007, Kepmenperind RI No. 256/MPP//KEP/7/ concerning Regulations for the Implementation of Franchise based on Regulation of the Minister of Trade No. 12/M-Dag/Per/3/2006 concerning Registration and Commercial Regulations. In implementing a franchise agreement there are several principles of agreement, namely (1) The principle of freedom of contract, (2) the principle of consensualism, (3) the origin of trust, (4) the principle of strength binding, (5) the origin of legal equality, (6) the principle of balance, (7) the principle of legal certainty, (8) the principle of decency, and (9) the principle of custom. Disputes in franchise agreements can be resolved by deliberation or consensus or through judicial institutions and the Alternative Dispute Arbitration Board.